Kinetic modelling of the reversible addition–fragmentation chain transfer polymerisation of N-isopropylacrylamide. (November 2019) - Luan, Bao; Li, Chao'en; Moad, Graeme; Muir, Benjamin W.; Zhu, Jin; Patel, Jim; Lim, Seng; Hao, Xiaojuan
Graphical abstract: Highlights: Kinetic modelling of N-isopropylacrylamide polymerisation was carried out. A simplified simulation method was proposed. The mechanistic rate coefficients were optimised. The modelling results accurately simulated the experimental data obtained. Abstract: Reversible addition–fragmentation chain transfer (RAFT) polymerisation is a complex process involving multiple fundamental reaction steps that makes estimation of rate coefficients and exact kinetic simulation problematical. In this paper, we show that the homopolymerisation of N -isopropylacrylamide (NIPAM) can be kinetically modelled using a much-simplified method involving only a few kinetic parameters. The experimental polymerisation of NIPAM was performed with 4-cyano-4-(phenylcarbonothioylthio)pentanoic acid as the RAFT agent and 4, 4′-azobis(4-cyanopentanoic acid) as the initiator in dioxane at three different temperatures (60, 70 and 80 °C) with the initial [RAFT]:[initiator] ratio kept at 5:1 and different initial [monomer]:[RAFT] ranging from 100:0.2 to 100:1. Our method for the kinetic simulation makes use of a pseudo-concentration of polymer, in which all chains are assumed to have the same molar mass equal to the average molar mass M n . With these approximations, the apparent rate coefficients for propagation, termination and initiator decomposition ( k p, app, k t, app and k d, app respectively) and three fitting parameters, αp (ratio of propagating radicals to macroRAFT agent), αk p (ratio k rein, app / k p, app ), and αkt (exponent describing the chain length dependence of k t ) were optimised. Our modelling results adequately simulated the experimental polymerization kinetics. Values of k t, app, k d, app, αp, αkp, αkt appeared essentially independent of [monomer]:[RAFT] and the values k t, app, k d, app and αkt were consistent in magnitude with literature values of the corresponding k t, α and k d f . Retardation associated with the RAFT process is encompassed in the value of k p, app, which was strongly dependent on [monomer]:[RAFT], with higher k p, app and R p being observed for higher [monomer]:[RAFT].